DAMPAK KENAIKAN HARGA KEDELAI TERHADAP IDUSTRI KECIL PENGOLAHAN TAHU DI KELURAHAN BATU KOTA KECAMATAN MALALAYANG MANADO - Taufik S. Damanik; Grace A.J. Rumagit; Paulus A. Pangemanan; Mex F.L. Sondakh (COCOS, 2014)
ABSTRACTThe objective of this research in to observe the effects before and after the increase of soybean prices to tofu processing small industries in Batu Kota Village, Malalayang sub District, Manado. Data collection was conducted over six months, from Februari 2014 until Juli 2014. Data obtained are primary and secondary data. Primary data obtained through the survey directly to the tofu enterprice in Batu Kota Village, Malalayang Sub District, Manado. Secondary data obtained through agencies associated with this research. Sampling was done by simple Saturated sampling technique, a total of 4 Respondents of small processing industry was sampled. The basic method used to see before and after the increase in soybean prices is that the next stage of your analysis descriptive in the form of tabulation, editing and processing of data by using Microsoft Excel Software.The results of this study indicated there was impact of price increases on small industrial soybean processing in Batu Kota Village, Malalayang Sub District, Manado. The impacts were in input factor price, decrease in the volume of production, the cost of the industry, the price of tofu, the size changes of tofu, revenue and profits of tofu entrepreneur. The increase of soybean prices reached 35.84 gratuity, tofu in Batu Kota still exist. This is due to changes in the size of tofu, besides tofu also has an informal partnership for the supply of raw materials with the tofu supplier there fore their industry still exist and feasible.Keywords : Frequency of production, informal Partnership, change of the size of the tof